Relações de interferência entre plantas daninhas e a cultura do grão-de-bico - Do Amaral, Carita Liberato [UNESP]; Pavan, Guilherme Bacarim [UNESP]; de Souza, Marcelo Claro; Martins, José Valcir Fidelis [UNESP]; Da Costa Aguiar Alves, Pedro Luis [UNESP] (My University, 2015)
The grains of chickpea consumed in Brazil are almost entirely imported. Considering that chickpeas presents conditions to be cultivated in some regions of Brazil, this study aimed to study interference of six weed plants (Amaranthus viridis, Bidens pilosa, Raphanus raphanistrum, Cyperus rotundus, Digitaria nuda and Eleusine indica) on the vegetative development of chickpeas. Thus, we evaluated the shoot length, number of leaves, leaf area, chlorophyll content and dry weight of leaves, stem and root of chickpeas. We observed a significant interference on the chickpeas’ development in coexistence with weeds. Among the weeds, D. nuda, E. indica and A. viridis were the most aggressive, highlighting the need for early control of weeds when in cultivation of chickpeas in areas with a history of high density of these weeds. The leaf area of chickpeas was the most affected trait by the coexistence with weeds, affecting the development of the crop.
Interference relationships between chick-peas crop and weeds
Keywords: Cicer arietinum; Coexistence; Competition; Crop management